Tamarind seed extract enhances epidermal wound healing - Mohamad, Mohd Yusof; Akram, Haris; Bero, Dinie Najwa; Rahman, Muhammad Tariqur (Canadian Center of Science and Education, 2012)
Traditional healing power of tamarind fruits and the established antioxidant activity of the seeds drive the present study. Wound healing efficiency of tamarind seed was evaluated. Different solvents: phosphate buffer saline (PBS), water, methanol and ethanol were used to prepare the extract. Circular wound was inflicted on the nape. 10 μl of 5 μg/ml of extract was applied topically twice daily. Wound area was measured using Adobe ®Photoshop C3 Extended version and the percentage of wound reduction was calculated. PBS extract treatment induced complete wound healing in shortest period (10 days) while water extract, methanol extract and Solcoseryl ointment treatment induced complete wound healing in 11 days and control groups without any treatment took 14 days to heal. Phytochemical screening and Bradford method for protein quantification reveals the presence of alkaloid, saponin and tannin in all samples except PBS extract which tested negative to tannin. Flavonoid tested positive in methanol and ethanol extracts. Keywords: Wound healing, Tamarind seed extract, Solcoseryl,